Analysis of Factors Affecting Banking Efficiency Level at Commercial Banks in Indonesia - Af’idah, Nancy Latifatul; Sholikah, Yuniati; Choiriyah, Agustina Fatimatul; Sujianto, Agus Eko (International Journal Labs, 2023)
One important aspect in the success of an enterprise is the level of efficiency. Efficiency is the relationship between managing the company's inputs and outputs optimally. This study aims to determine what factors affect the level of banking efficiency at commercial banks in Indonesia. The method used is quantitative descriptive where data is taken from data that has been published. The sample in this study was taken from one of the commercial banks in Indonesia, namely Bank Mandiri in 2018-2022. The result of this study is that CAR and LDR together do not have a significant effect on the level of banking efficiency in commercial banks in Indonesia, where CAR is positive and LDR is negative.